CHURCH AND CHURCH BUILDING: Interview-Based Meanings Among Minority Catholics, Pinang Parish, Tangerang, Indonesia - Fransiskus Sule; Karel Wunardi (QUAERENS: Journal of Theology and Christianity Studies, 2026)
This study investigates what the church building means for the Catholic faithful of Pinang Parish, Tangerang (Archdiocese of Jakarta). Using semi-structured interviews with seventeen parishioners and a phenomenological thematic analysis, it adopts a phenomenological–theological approach to interpret how the building is lived within everyday faith. Five themes emerged: identity, communion, stability, sacredness, and fulfillment. Participants describe the new church as making the community public and recognizable (“now we can point and say, this is our church”), gathering ministries into a stable locus for fellowship and service, and relieving the insecurity of rotating or provisional worship spaces. They also speak of an atmosphere that disposes reverence and of a sense of arrival after a long struggle for official permission to build. Wallenfang’s notion of paradox clarifies this experience: the church is held together as a concrete structure and as a sacramental sign—visible and fragile, yet experienced as mediating God’s dwelling that exceeds visibility. For a minority community, the building thus embodies perseverance and joy while reconfiguring how the faithful understand themselves as Church. The study advances ecclesiological reflection on sacred architecture by offering a bottom-up account of how lay experience and contested building processes shape ecclesial self-understanding, with relevance to wider debates on disputed worship spaces in minority contexts.